On the evolution of weak discontinuities in radiative magnetogasdynamics - Singh L.P.; Husain A.; Singh M. (My University, 2025)
A method of wavefront analysis is used to analyze the formation of shock waves in a two-dimensional steady supersonic flow past plane and axisymmetric bodies in radiative magnetogasdynamics. The gas is assumed to be perfectly conducting and to be permeated by a magnetic field orthogonal to the trajectories of the gas particles. The medium is taken to be sufficiently hot for the effects of thermal radiation to be significant, which is treated by the optically thin approximation to the radiative transfer equation. Transport equations, which lead to the determination of the distance at which the first characteristic could intersect with a successive one and also to conditions, which insure that no shock will ever evolve on the wave front, are derived. The effect of upstream flow Mach number and the magnetic field strength on the behavior of the wavefront are examined. © 2010 Elsevier Ltd. All rights reserved.